Effects of Using an Early Childhood Teacher Training Program on Organizing Loose Parts Play to Enhance Soft Skills for Kindergarten Students in Sakaeo Province - Pantuworakul, Kullachat; Nuansri, Mesa; Papol, Khantharot (Ratchaphruek Journal, 2025)
The purposes of this research were: 1) To examine the outcomes of implementing an early childhood teacher training program on organizing loose parts play to enhance soft skills for kindergarten students; and 2) To compare the soft skills of kindergarten students before, after, and during the follow-up stage of organizing loose parts play. The research sample comprised 29 early childhood teachers and 488 kindergarten students in schools under the jurisdiction of the Sakaeo Primary Educational Service Area Office 1 selected through muti-stage random sampling. Research instruments included a test, survey forms, satisfaction questionnaires, and a soft skills assessment form. Data analysis involved the use of frequency distribution, percentage, mean, standard deviation, t-test, and repeated measures. The findings revealed that: 1) After the training, not only the early childhood teachers had significantly higher average knowledge scores at the .05 level of statistical significance, but also the early childhood teachers demonstrated increased behaviors in managing loose parts play across all items, ranging from 20.69% to 75.86%, and also expressed a high level of satisfaction with the overall utilization of the program after the training. 2) The kindergarten students had higher average soft skills scores than before the program implementation and higher average soft skills scores at the follow-up stage than before the implantation at the .05 level of statistical significance.